P128 Practise Patterns in Idiopathic Pulmonary Fibrosis: Results of a UK Physician Survey. (19th November 2012) - Kausar, I; Cameron, R; Eastmond, NC
Abstract : Introduction and objectives: Idiopathic pulmonary fibrosis (IPF) is a rare, progressive, fibrotic lung disorder that results in reduced lung capacity, disability and ultimately death. Its rarity, and the fact that many of its initial symptoms are common to other lung diseases, mean that it is often mis-diagnosed and patients can experience wide variations in standards of care. We conducted a survey of pulmonary physicians to better understand practise patterns and unmet needs in IPF . Methods: In December 2010 – January 2011, a structured, quantitative survey was conducted with lung specialists in IPF and non-IPF specialist centres principally in five EU countries (Germany, Italy, Spain, UK, France [5EU]). The survey was extended to a further five countries where fewer physicians were targeted. The survey covered clinical practise patterns over the preceding 12 months. Data from the UK are presented here. Results: The 5EU sample included 232 participating physicians. Of these, 26 were from the UK, with 15 from specialist IPF centres, and 11 from general lung clinics. Among the UK clinics, 46% of patients had stable IPF, versus 56% with progressive disease (51% versus 49% respectively for 5EU). Triple therapy (steroid + immunosuppressant + N-acetylcysteine [NAC]) was prescribed for 31% of UK patients versus 25% for 5EU. Nineteen percent of UK IPF patients went untreated, and a further 10% received palliative care. Steroid monotherapy was used in another 10% of UK patients, and 11% received steroid + immunosuppressant. NAC + steroids were used in only 5% of patients, and NAC alone in 6%. Conclusion: IPF is a serious condition, but no standard therapy exists, and many patients receive no treatment or palliative care only. Current therapies are ineffective and unproven. At the time of the survey triple therapy remained prevalent; however, concerns have now been raised regarding AEs and risks of death and hospitalisation. There is therefore an unmet need for effective and well-tolerated therapies to enable a greater range of patients to be treated with agents that have been proven to be safe and effective in clinical trials.